Helium induced microstructure damage, nano-scale grain formation and helium retention behaviour of ZrC. (15th January 2019) - Agarwal, Shradha; Bhattacharya, Arunodaya; Trocellier, Patrick; Zinkle, Steven J.
Abstract: Transition-metal ultra-high temperature ceramics are promising materials for nuclear structural applications. However, an understanding of their response to high-temperature irradiation and helium is vastly limited. This paper presents a study of helium effects in zirconium carbide (ZrC) by performing room temperature 3 MeV 3 He + ion irradiations up to 5 × 10 20 ions m −2 (∼1.8 at.% at peak) and high-temperature annealing (1273–1873 K), coupled with state-of-art characterization using transmission electron microscopy (TEM), scanning electron microscopy (SEM) and nuclear reaction analysis (NRA). We reveal that ZrC is susceptible to irradiation damage in terms of helium bubble formation. After annealing at 1373 K, tiny bubbles (1–2 nm) formed aligned clusters which were highly over-pressurized, producing strain contrast in TEM. At 1773 K, significant bubble growth occurred. Additionally, at 1773 K, a combined TEM/SEM analysis revealed dramatic matrix damage due to helium-induced surface blistering. Underneath blister caps, the microstructure evolved into ultra-fine nano-scale grains similar to high burn-up structures observed in nuclear fuels, but consisting of numerous nano-cracks. We hypothesize that such structures are formed due to high gas pressure build-up and its subsequent release. This phenomenon initiated at the grain boundaries. Blister top surface consisted of inter-granular and trans-granular cracks. NRA depth profiling revealed that helium was present as double peaks with major portion lying at the end-of-the-range (EOR) and the rest as TEM invisible clusters in a shoulder extending to the surface. ZrC started releasing helium after 1373 K. Helium release increased significantly at higher temperatures, with majority helium loss occurring from EOR rather than from near-surface regions. Graphical abstract: Image 1